Solar Powered Autonomous RC Robot - Musa, Muhammad Akmal; Mashori, Sumaiya (Progress in Engineering Application and Technology, 2023)
Modern farming using sensor and control technology, renewable energy, and agricultural robots aims to produce higher-quality products at lower costs, reduce labor workload, and enhance efficiency and safety compared to traditional methods. The study aimed to develop a robot that used Photo-voltaic (PV) panels for low-power recharging and efficient sustainability while integrating a reliable wireless link for seamless robot-controller communication and monitoring. This paper discussed new strategies for replacing humans in agricultural operations, including structural design, robot control systems, and experimental results on renewable energy, mobility, durability, and safety. The robot system used a battery and PV module for power supply, with the L298N motor driver and Raspberry Pi 4B controller. The system software, Thonny IDE, drove the robot in either automatic or manual mode and transported the harvested product to the collection area. Besides, it has been tested in several experiments to ensure the PV panel was a reliable and sustainable source of low-power recharging for the robot, the robot’s durability to transport the 10kg weight, and the runtime of the robot during a given task was also evaluated. From the result, it can be concluded that the robot can be automated charging using the PV module, and the runtime of the time working can be extended if using a proper battery. Further improvements included adding sensors for accurate movement measurements and strengthening the robot’s body chassis for stability and future lifting capabilities over 10kg.